The association between Alu hypomethylation and severity of type 2 diabetes mellitus - Thongsroy, Jirapan (Clin Epigenetics, 2017)
BACKGROUND: Cellular senescence due to genomic instability is believed to be one of the mechanisms causing health problems in diabetes mellitus (DM). Low methylation levels of Alu elements or Alu hypomethylation, an epigenomic event causing genomic instability, were commonly found in aging people and patients with aging phenotypes, such as osteoporosis. RESULTS: We investigate Alu methylation levels of white blood cells of type 2 DM, pre-DM, and control. The DM group possess the lowest Alu methylation (P < 0.001, P < 0.0001 adjusted age). In the DM group, Alu hypomethylation is directly correlated with high fasting blood sugar, HbA1C, and blood pressure. CONCLUSION: Genome-wide hypomethylation may be one of the underlining mechanisms causing genomic instability in type 2 DM. Moreover, Alu methylation levels may be a useful biomarker for monitoring cellular senescence in type 2 DM patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-017-0395-6) contains supplementary material, which is available to authorized users.